Rehabilitación respiratoria en pacientes adultos post trasplante pulmonar. - Acán Acán, Jhonatan Paul (2025)
The aim of this research, “Respiratory rehabilitation in adult post pulmonary trasplant patients”, was to develop a literature review on the efficiency of respiratory rehabilitation in adult post pulmonary trasplant patients, with the purpose to have updated evidence to support improvement in their quality of life and early reintegration to their daily life activities. The purpose of lung trasplantation is to improve the life and life condition of individuals with a gradual and irreversible lung disease. After the intervention, it influences and generates alterations in several elements of respiratory physiology. Any of these modifications cause a reduction in lung volumes, a reduction in tolerance to effort, dyspnea and a reduction in quality of life, reason why we require respiratory recovery. Respiratory Rehabilitation is a speciality within the field of Physiotherapy, Respiratory Physiotherapy has been used for several years to refer to the different practices, techniques, procedures and instruments which are to be applied in pulmonary pathologies or related to the respiratory system. Post-operative recovery is essential, it allows evaluating the physical situation and applying respiratory readaptation in all stages contributes to improve the capacity of the respiratory and skeletal muscle system, the level of functional capacity, physical condition and survival after surgery. This research work is based on a bibliographic type documentary review with the search of articles supported by Web databases such as: PubMed, Scielo, Scopus, Elsevier, ScienceDirect, Dialnet. The selected articles complied with different parameters of inclusion and exclusion criteria. We obtained 25 articles that fulfilled the criteria of the PEDro scale greater than 6 for the development of the research. The evidence allows us to conclude that respiratory rehabilitation after lung trasplantation in adult population has demonstrated satisfactory results on the efficiency of the intervention, as well as the improvement of symptomatology, increase in muscle strength, increase in respiratory capacity, increase in functional activity and reintegration to daily activities.